Analysis Of Technological Processes In CottonTextile Clusters - Saparbaeva Navba'har Daribay qizi; Paluanov Bakhtiyar Aralbaevich (Peerian Journals Publishing, 2025)
This article analyzes the technological systems of production processes in cottontextile clusters organized in the Republic of Uzbekistan. Further, recommendations were given on the development of technological parameters of the compact spinning system for cottontextile clusters.
Keywords: Cotton-textile clusters; cluster theory; cotton fiber